Peritoneal transformation shortly after kidney transplantation in pediatric patients with preceding chronic peritoneal dialysis - Zhang, Conghui; Bartosova, Maria; Marinovic, Iva; Schwab, Constantin; Schaefer, Betti; Vondrak, Karel; Ariceta, Gema; Zaloszyc, Ariane; Ranchin, Bruno; Taylan, Christina; Büscher, Rainer; Oh, Jun; et al. (Nephrology, dialysis, transplantation, 2023)
BACKGROUND: The unphysiological composition of peritoneal dialysis (PD) fluids induces progressive peritoneal fibrosis, hypervascularization and vasculopathy. Information on these alterations after kidney transplantation (KTx) is scant. METHODS: Parietal peritoneal tissues were obtained from 81 pediatric patients with chronic kidney disease stage 5 (CKD5), 72 children on PD with low glucose degradation product (GDP) PD fluids, and from 20 children 4-8 weeks after KTx and preceding low-GDP PD. Tissues were analyzed by digital histomorphometry and quantitative immunohistochemistry. RESULTS: While chronic PD was associated with peritoneal hypervascularization, after KTx vascularization was comparable to CKD5 level. Submesothelial CD45 counts were 40% lower compared with PD, and in multivariable analyses independently associated with microvessel density. In contrast, peritoneal mesothelial denudation, submesothelial thickness and fibrin abundance, number of activated, submesothelial fibroblasts and of mesothelial-mesenchymal transitioned cells were similar after KTx. Diffuse peritoneal podoplanin positivity was present in 40% of the transplanted patients. In subgroups matched for age, PD vintage, dialytic glucose exposure and peritonitis incidence, submesothelial hypoxia-inducible factor 1-alpha abundance and angiopoietin 1/2 ratio were lower after KTx, reflecting vessel maturation, while arteriolar and microvessel p16 and cleaved Casp3 were higher. Submesothelial mast cell count and interleukin-6 were lower, whereas transforming growth factor-beta induced pSMAD2/3 was similar as compared with children on PD. CONCLUSIONS: Peritoneal membrane damage induced with chronic administration of low-GDP PD fluids was less severe after KTx. While peritoneal microvessel density, primarily defining PD transport and ultrafiltration capacity, was normal after KTx and peritoneal inflammation less pronounced, diffuse podoplanin positivity and profibrotic activity were prevalent.
Keywords: Glucose; glukosa; Peritoneal Dialysis; transplantace ledvin; Renal Dialysis; Dialysis Solutions; Peritonitis; dítě; Child; peritoneum; peritoneální dialýza; Kidney Transplantation; Humans; peritonitida; Peritoneum; dialyzační roztoky; dialýza ledvin; Kidney Failure, Chronic; chronické selhání ledvin; lidé